Collateral circulation predicts 3-month functional outcomes of subacute ischemic stroke patients: A study combining arterial spin labeling and MR angiography. Issue 160 (March 2023) - Wu, Di; Zhou, Yiran; Zhang, Guiling; Shen, Nanxi; Lu, Jun; Yan, Su; Xie, Yan; Gao, Luyue; Liu, Yufei; Liu, Chengxia; Zhang, Shun; Zhu, Wenzhen
Highlights: Arterial transit artifact on ASL images indicates leptomeningeal collaterals which provide extra information about the collaterals compared to angiographic methods. Good circulation on MRA indicates fast flow and preserved perfusion. The combination of ASL and MRA could provide a useful method to predict functional outcomes of subacute ischemic stroke patients and guide therapeutic management. Abstract: Objective: Collateral circulation could help preserve the blood supply and protect penumbra in ischemic stroke (IS), critical for late-window therapeutic decisions and clinical outcomes. In this study, we aimed to investigate the prognostic value of two collateral indexes measured by arterial spin labeling (ASL) and MR angiography (MRA) in subacute IS patients. Materials and Methods: Fifty-five subacute IS patients with large artery atherosclerosis were retrospectively collected. Arterial transit artifact (ATA) on ASL and good circulation (GC) on MRA were ranked as markers of leptomeningeal collaterals and fast collaterals, respectively. Volume and relative cerebral blood flow (rCBF) of infarct and hypoperfusion area were calculated. Stroke severity was determined by baseline- and discharge- National Institute of Hospital Stroke Scale (NIHSS). Functional independence (FI) was defined as 3-month modified Ranking Scale ≤2. Univariate analyses and multivariable logistic regression analyses were conducted to identify the independent predictors of FI. Results: Thirty-eight patients (69.1 %) presented ATA and 29 (52.7 %) patients presented GC. Univariate analyses showed that baseline-NIHSS, discharge-NIHSS, rCBF of infarct, presence of ATA and GC were associated with FI ( P < 0.05). After multivariable adjustment, ATA (adjusted Odds Ratio [OR]: 13.785, 95 % CI: 2.608–72.870, P = 0.002) and GC (adjusted OR: 8.317, 95 % CI: 1.629–42.454, P = 0.011) remained independent predictors of FI. Besides, patients with both ATA and GC had the highest frequencies of FI while patients with neither of them showed the lowest (94.7 % vs 14.3 %, P < 0.001), indicating a positive synergistic effect between ATA and GC. Conclusion: The combination of ASL and MRA simultaneously reflects leptomeningeal collaterals and fast collaterals, providing a useful method to predict functional outcomes of subacute IS patients.